Emerging roles of sphingosylphosphorylcholine in modulating cardiovascular functions and diseases. (December 2018) - Ge, Di; Yue, Hong-wei; Liu, Hong-hong; Zhao, Jing
Abstract Sphingosylphosphorylcholine (SPC) is a bioactive sphingolipid in blood plasma that is metabolized from the hydrolysis of the membrane sphingolipid. SPC maintains low levels in the circulation under normal conditions, which makes studying its origin and action difficult. In recent years, however, it has been revealed that SPC may act as a first messenger through G protein-coupled receptors (S1P1-5, GPR12) or membrane lipid rafts, or as a second messenger mediating intracellular Ca2+ release in diverse human organ systems. SPC is a constituent of lipoproteins, and the activation of platelets promotes the release of SPC into blood, both implying a certain effect of SPC in modulating the pathological process of the heart and vessels. A line of evidence indeed confirms that SPC exerts a pronounced influence on the cardiovascular system through modulation of the functions of myocytes, vein endothelial cells, as well as vascular smooth muscle cells. In this review we summarize the current knowledge of the potential roles of SPC in the development of cardiovascular diseases and discuss the possible underlying mechanisms.